Straightforward systematic approach for fuel efficiency and emissions assessment in automotive systems - Nonato, Fabio; MacEdo, Gabriel Figlie [UNESP] (SAE International, 2011)
At this time, each major automotive market bares its own standards and test procedures to regulate the vehicle green house gases emissions and, thus, fuel consumption. Hence, much are the ways to evaluate the overall efficiency of motor vehicles. The majority of such standards rely on dynamometer cycle tests that appraise only the vehicle as a whole, but fail to assess emissions for each component or sub-system. Once the amount of work generated by the power source of an ICE vehicle to overcome the driving resistance forces is proportional to the energy contained in the required amount of fuel, the power path of the vehicle can be straightforwardly modeled as a set of mechanical systems, and each sub-system evaluated for its share on the total fuel consumption and green house gases emission. This procedure enables the estimation of efficiency gains on the system due to improvement of particular elements on the vehicle's driveline. In this work a simple systematic mechanical model of an arbitrary smallsized hatch back was assembled and total required energy calculated for different regulatory cycles. All the modeling details of the energy balance throughout the system are presented. Afterward, each subsystem was investigated for its role on the fuel consumption and the generated emission quantified. Furthermore, the application of the modeling technique for different sets of sub-systems was introduced. Copyright © 2011 SAE International.
Keywords: Automotive markets; Automotive Systems; Cycle tests; Drivelines; Efficiency gain; Fuel efficiency; Mechanical model; Mechanical systems; Modeling technique; Motor vehicle; Overall efficiency; Power path; Power sources; Resistance force; Sub-systems; Test procedures; Greenhouse gases; Testing; Vehicles